Nano-silver antibacterial hydrophobic liquid as well as preparation method and application thereof

A nano-silver antibacterial hydrophobic liquid is applied to glass surfaces, addressing bacterial contamination and water spotting issues by forming a durable, eco-friendly coating that is cost-effective and suitable for large-scale applications.

CN120309184APending Publication Date: 2025-07-15YULIN NORMAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510441024.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

Existing glass surfaces, particularly in mobile devices, suffer from bacterial contamination and water spotting due to their hydrophilic nature, necessitating costly and complex treatments that are not suitable for large-scale applications, and existing anti-fouling and antibacterial coatings are environmentally harmful and inefficient.

Method used

A method to prepare a nano-silver antibacterial hydrophobic liquid by mixing silver nanoparticles with a silane coupling agent, which forms a stable and durable coating on glass surfaces, providing both antibacterial and hydrophobic properties through a simple application process.

Benefits of technology

The solution achieves long-lasting antibacterial and hydrophobic effects on glass surfaces without using harmful fluorine-based compounds, suitable for large-scale applications and easy DIY implementation, enhancing user experience and hygiene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120309184A_ABST
    Figure CN120309184A_ABST
Patent Text Reader

Abstract

The invention provides nano-silver antibacterial hydrophobic liquid as well as a preparation method and application thereof. The preparation method comprises the following steps: dissolving silver nitrate in a first anhydrous alcohol solvent to prepare a solution A, and dissolving polyvinylpyrrolidone in a second anhydrous alcohol solvent to prepare a solution B; the solution A and the solution B are mixed and subjected to ultrasonic treatment for 20-80 minutes, and the high-concentration alcohol-based nano-silver antibacterial liquid is obtained; adding low-viscosity hydroxyl silicone oil, polyvinyl acetal and hydrogen-containing silicone oil into a third anhydrous alcohol solvent, and stirring to obtain a transparent and colorless solution; then adding concentrated sulfuric acid, continuing stirring reaction, finally adding siloxane, and stirring to obtain hydrophobic liquid; and adding the high-concentration alcohol nano-silver antibacterial liquid into the hydrophobic liquid, stirring for 20-50 minutes, and uniformly mixing to obtain the nano-silver antibacterial hydrophobic liquid. The antibacterial hydrophobic liquid provided by the technical scheme of the invention has antibacterial and hydrophobic anti-fingerprint functions, does not contain fluorine, is simple in preparation process, and is suitable for modification of antibacterial and hydrophobic functions of various types of glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and particularly to a nano silver antibacterial hydrophobic liquid, a preparation method thereof and an application thereof. Background Art

[0002] Due to its excellent light transmittance, wear resistance, chemical stability, aesthetics, etc., glass is widely used in many fields such as mobile phones, computers, automobiles, buildings, and medical treatment. Since glass is usually hydrophilic, its surface is easily contaminated and bacteria are likely to breed. Research shows that the screen of an ordinary mobile phone can carry more than 20 kinds of bacteria, and the number is as high as hundreds to tens of thousands per square centimeter, approaching the number of a "mobile bacteria culture dish", which is more than 10 times that of a toilet seat. In addition, due to the hydrophilicity of glass, its use touch feeling is poor, and fingerprints and water marks are very likely to be left on the surface, which will affect the appearance and use experience, and greatly increase the frequency and difficulty of cleaning. Therefore, antibacterial and hydrophobic treatment of the glass surface, reducing screen stains and the breeding of germs, preventing the spread of germs, and improving the clarity and beauty of the display screen have become an urgent need for people's healthy life.

[0003] Currently, in terms of the antibacterial application of mobile phone glass, the screen cover of Xiaomi 11 Ultra uses Corning Ag-ion doped green silicate glass, Sony Xperia 1Ⅲ uses Schott nano SiO2-Ag composite coating glass, Vivo X70Pro+ uses the fully laminated antibacterial OLED screen of Lens Technology, Honor Magic3 to the Ultimate Edition uses the graphene-enhanced antibacterial film of BYD Optoelectronics, and the "Kunlun antibacterial glass" used in Huawei Mate 60RS is obtained by melting and injecting rare earth cerium elements at 1400°C. It can be seen that the antibacterial performance of mobile phone glass is given by changing the composition of the material as a whole, which has the advantages of long life and good performance. Of course, the cost is relatively high, and it only has a single antibacterial function. In particular, this overall replacement method of glass antibacterial is difficult to simply and quickly functionalize the ordinary mobile phone glass with a huge market stock.

[0004] In terms of hydrophobic and anti-fouling of mobile phone glass, fluorine-containing compounds are mostly used, such as Optool DSX and Optool AES of Daikin in Japan, 3M TM Fluorochemical Coating FC-4430 of 3M Company in the United States, and AF coating of Schott in Japan; in China, there are UR-AF2000 series of Zhuhai Yourun and SDKAF Coating of Jiangsu Stick. Usually, the vacuum coating process or the spraying / dipping + heating composite process is used to achieve the hydrophobic and anti-fingerprint function of the glass surface, which needs to be operated on special equipment in the factory. Such products are not environmentally friendly due to containing fluorine, and the construction is complex, and they are not suitable for the functionalization treatment of mobile phone glass with a huge market stock. Summary of the Invention

[0005] In view of the above technical problems, the present invention discloses a nano-silver antibacterial hydrophobic liquid, a preparation method thereof and an application thereof, which can be applicable to the antibacterial and hydrophobic dual functions of existing mobile phone glasses in the market, and has the advantages of simple construction operation, fluorine-free, low price, long-term antibacterial property and excellent hydrophobicity.

[0006] For this purpose, the technical solution adopted by the present invention is as follows:

[0007] A preparation method of a nano-silver antibacterial hydrophobic liquid, comprising the following steps:

[0008] Step S1: Dissolve silver nitrate in a first anhydrous alcohol solvent to prepare solution A, and dissolve polyvinylpyrrolidone (PVP) in a second anhydrous alcohol solvent to prepare solution B; mix solution A and solution B, and perform ultrasonic treatment for 20 - 80 minutes to obtain a high-concentration alcohol-based nano-silver antibacterial liquid, wherein the concentration of silver in the high-concentration alcohol-based nano-silver antibacterial liquid is 2.8 - 5.5 wt.%.

[0009] Step S2: Add low-viscosity hydroxy silicone oil, polyvinyl acetal and hydrogen-containing silicone oil to a third anhydrous alcohol solvent and stir to obtain a transparent and colorless solution; then add concentrated sulfuric acid and continue stirring and reacting for 40 - 120 minutes, and finally add siloxane and stir for 10 - 40 minutes to obtain a hydrophobic liquid; wherein, the hydroxy content of the low-viscosity hydroxy silicone oil is 8 - 10 wt%, and the viscosity is 100 - 800 CS; the hydrogen content of the hydrogen-containing silicone oil is 1 - 2 wt%, and the viscosity is less than 200 CS.

[0010] Step S3: Add the high-concentration alcohol-based nano-silver antibacterial liquid prepared in Step S1 to the hydrophobic liquid prepared in Step S2, and stir for 20 - 50 minutes to mix evenly to obtain a nano-silver antibacterial hydrophobic liquid; in the nano-silver antibacterial hydrophobic liquid, the mass concentration of nano-silver particles is 150 - 500 PPM.

[0011] In the above technical solution, the high-concentration alcohol-based nano silver antibacterial liquid in step S1 is prepared by the ultrasonic-assisted polyol reduction method. Under the action of the local high temperature, high pressure, strong shock wave and micro-jet generated by the ultrasonic cavitation effect, on the one hand, the thermal effect of ultrasonic waves triggers alcohol thermal reduction; on the other hand, ultrasonic waves cause the decomposition of alcohol solvents and polyvinylpyrrolidone to generate reducing electrons or organic free radicals, which play an auxiliary reduction role; furthermore, the mechanical vibration and micro-jet action of ultrasonic waves can effectively disperse nano silver particles and prevent agglomeration, thereby controlling the particle size and morphology. Due to the above multiple synergistic effects, the silver nano particles in the high-concentration nano silver antibacterial liquid prepared by the present invention have a small size, uniform morphology and good dispersibility. Under the preparation conditions of the present invention, polyvinylpyrrolidone (PVP) mainly acts as a surfactant and dispersant to stabilize nano silver and prevent nano silver particles from agglomerating.

[0012] In the preparation of the hydrophobic liquid in step S2 and the antibacterial hydrophobic liquid in step S3, a hydrophobic coating is prepared by the condensation reaction of hydrogen-containing silicone oil and hydroxyl silicone oil under acidic conditions. Since the hydroxyl groups (-OH) and acetal groups (-O-CH2-O-) in the molecular chain of polyvinyl acetal have polarity, they can form hydrogen bonds with the silanol groups (Si-OH) on the glass surface and form hydrogen bonds or dipole-dipole interactions with the metal surface. In the solution of the present invention, it acts as a good binder for glass and metal, firmly adheres the hydrophobic coating to the clean glass surface, and anchors the nano silver particles in the hydrophobic coating, playing the functions of silver ion slow release and long-term antibacterial. In addition, the residual hydroxyl groups (-OH) in polyvinyl acetal can also undergo a sulfonation reaction with concentrated sulfuric acid, and the generated sulfate ester group (-O-SO3H) has strong coordination ability and can bind to the surface of nano silver in the following ways: one is lone pair electron coordination, and the oxygen atom with lone pair electrons in the sulfonic acid group forms a coordination bond with the uncoordinated Ag o atoms on the surface of Ag nano particles, enhancing particle dispersion; the other is electrostatic adsorption. Under acidic or neutral conditions, the sulfonic acid group (-SO3---H + ) ionizes H + , and the negatively charged -SO3 - undergoes electrostatic attraction with the positively charged surface of Ag nano particles (due to the formation of a small amount of Ag + ) due to surface oxidation. This further prevents the agglomeration of silver nano particles, improves the anchoring strength of silver nano particles in the hydrophobic coating, and ensures the long-term antibacterial function of the hydrophobic coating. The added siloxane acts as a capping agent and can react with the residual hydroxyl groups (-OH) in polyvinyl acetal species and the silanol groups (-SiOH) in silicone oil under acidic conditions to eliminate the hydrophilic polar groups in the hydrophobic coating and further improve the hydrophobicity of the coating.

[0013] As a further improvement of the present invention, in step S1, the first anhydrous alcohol solvent and the second anhydrous alcohol solvent are one or a mixture of more than one of ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, glycerol, and butanol. Further, the first anhydrous alcohol solvent contains ethylene glycol. Further, the first anhydrous alcohol solvent is ethanol and ethylene glycol, and the second anhydrous alcohol solvent is absolute ethanol. Further, in the first anhydrous alcohol solvent, the mass ratio of ethanol to ethylene glycol is 0.75 - 1.25:1.

[0014] As a further improvement of the present invention, the polyvinylpyrrolidone is one or a mixture of more than one of those with a polymerization degree of K17, K30, K60, and K90.

[0015] As a further improvement of the present invention, in step S1, solution A and solution B are mixed under ultrasonic conditions; further, solution A is quickly poured into the container containing solution B.

[0016] As a further improvement of the present invention, in step S1, the mass ratio of silver nitrate, PVP, the total of the first anhydrous alcohol solvent and the second anhydrous alcohol solvent is 1:0.6 - 1.5:10 - 20.

[0017] As a further improvement of the present invention, in step S1, the frequency of the ultrasonic wave is 40KHz, and the power density is 0.3 - 1.0W / cm 2 。

[0018] As a further improvement of the present invention, in step S2, the mass ratio of the third anhydrous alcohol solvent, low-viscosity hydroxy silicone oil, polyvinyl acetal, hydrogen-containing silicone oil, concentrated sulfuric acid, and siloxane is 100:4 - 10:0.5 - 2.0:2 - 8:1 - 4:0.1 - 1.0.

[0019] As a further improvement of the present invention, in step S2, the third anhydrous alcohol solvent is one or a mixture of more than one of ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, glycerol, and butanol.

[0020] As a further improvement of the present invention, in step S2, the polyvinyl acetal is one of 107 glue, 108 glue, polyvinyl acetal of methyl and ethyl, and polyvinyl butyral.

[0021] As a further improvement of the present invention, in step S2, the siloxane is at least one of polydimethylsiloxane, hexamethyldisiloxane, octamethylcyclotetrasiloxane, and hexamethylcyclotrisiloxane.

[0022] As a further improvement of the present invention, in step S2, the low-viscosity hydroxy silicone oil, polyvinyl acetal, and hydrogen-containing silicone oil are added to the third anhydrous alcohol solvent and stirred in a constant-temperature water bath, and the temperature of the water bath is 25 - 50°C.

[0023] As a further improvement of the present invention, in step S3, the mass ratio of the high-concentration alcohol-based nano silver antibacterial liquid to the hydrophobic liquid is 0.3 - 1.5:100.

[0024] The present invention also discloses a nano silver antibacterial hydrophobic liquid, which is prepared by using the preparation method of the nano silver antibacterial hydrophobic liquid as described above.

[0025] The present invention also discloses the application of the nano silver antibacterial hydrophobic liquid as described above, which is used for coating on the glass surface to endow the glass surface with antibacterial and hydrophobic functions.

[0026] As a further improvement of the present invention, the application of the nano silver antibacterial hydrophobic liquid includes the following steps:

[0027] Step S11, clean the glass surface to obtain a clean glass surface; further, clean the glass surface successively with clean water and absolute ethanol to remove surface contaminants and oil stains, etc., and wait for the absolute ethanol to volatilize before standing, so as to obtain a clean glass surface.

[0028] Step S12, spray or drop the nano silver antibacterial hydrophobic liquid on the glass surface, and evenly spin-coat the nano silver antibacterial hydrophobic liquid on the glass surface with a dust-free cloth or a cleaning sponge.

[0029] Step S13, wait for the absolute alcohol solvent to volatilize before standing, and a glass surface with both antibacterial and hydrophobic functions is obtained. The S2 step can be repeated several times according to needs to obtain a glass surface with better antibacterial and hydrophobic functions.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] The antibacterial hydrophobic liquid of the technical solution of the present invention has both antibacterial and hydrophobic and fingerprint-proof functions, and does not contain fluorine, which is more environmentally friendly; the preparation process is simple, no special dedicated equipment is required, the production cost is low, the usage method is simple, and it is especially suitable for the antibacterial and hydrophobic function transformation of various existing glasses in the market. Moreover, it can be constructed repeatedly, which is convenient for the restoration and long-term effectiveness of the antibacterial and hydrophobic functions of the glass surface, and has both functional integration and application universality. Further, the antibacterial hydrophobic liquid prepared by the present invention is especially suitable for the DIY needs of the huge existing market, and can be widely applied to the antibacterial and anti-fouling protection needs in the fields of mobile terminals, automotive glass, architectural glass, bathroom glass, medical glass, etc. Description of the Drawings

[0032] Figure 1 It is the laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 1 of the present invention.

[0033] Figure 2It is the transmission electron microscope photo of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 1 of the present invention; among them, (a) and (b) are photos at different magnifications.

[0034] Figure 3 It is the photo of the inhibition zone test of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 1 of the present invention; (a) to (d) are respectively the photos of the inhibition zone tests of the four samples in Example 1.

[0035] Figure 4 It is the photo of the antibacterial rate test of Escherichia coli of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 1 of the present invention; among them, (a) is the antibacterial result diagram of Example 1, and (b) is the blank control picture.

[0036] Figure 5 It is the schematic diagram of the use of the nano silver antibacterial hydrophobic liquid in Example 1 of the present invention; among them, (a) is the contaminated mobile phone glass, (b) is the cleaned glass, and (c) is the effect after coating with the antibacterial hydrophobic liquid.

[0037] Figure 6 It is the comparison photo of the hydrophobic angles before and after coating the antibacterial hydrophobic liquid on the glass surface in Example 1 of the present invention.

[0038] Figure 7 It is the laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 2 of the present invention.

[0039] Figure 8 It is the detection result of the hydrophobic angles before and after coating the antibacterial hydrophobic liquid on the glass surface in Example 2 of the present invention.

[0040] Figure 9 It is the laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 3 of the present invention.

[0041] Figure 10 It is the detection result of the hydrophobic angles before and after coating the antibacterial hydrophobic liquid on the glass surface in Example 3 of the present invention.

[0042] Figure 11 It is the laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 4 of the present invention.

[0043] Figure 12 It is the detection result of the hydrophobic angles before and after coating the antibacterial hydrophobic liquid on the glass surface in Example 4 of the present invention.

[0044] Figure 13 It is the laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 5 of the present invention.

[0045] Figure 14 It is the detection result of the hydrophobic angles before and after coating the antibacterial hydrophobic liquid on the glass surface in Example 5 of the present invention.

[0046] Figure 15 It is the laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 6 of the present invention.

[0047] Figure 16 It is the detection result of the hydrophobic angle before and after coating the antibacterial hydrophobic liquid on the glass surface in Example 6 of the present invention.

[0048] Figure 17 It is the laser particle size diagram of the nano silver antibacterial liquid prepared in Comparative Example 1 of the present invention.

[0049] Figure 18 It is the detection result of the hydrophobic angle before and after coating the antibacterial hydrophobic liquid on the glass surface in Comparative Example 1 of the present invention.

[0050] Figure 19 It is the laser particle size diagram of the nano silver antibacterial liquid prepared in Comparative Example 2 of the present invention.

[0051] Figure 20 It is the detection result of the hydrophobic angle before and after coating the antibacterial hydrophobic liquid on the glass surface in Comparative Example 2 of the present invention. Detailed implementation manners

[0052] The following further details the preferred embodiments of the present invention.

[0053] Example 1

[0054] A nano silver antibacterial hydrophobic liquid, and its preparation method includes the following steps:

[0055] Step S1, preparation of high-concentration alcohol-based nano silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 6 g of absolute ethanol and 8 g of ethylene glycol to prepare solution A, dissolve 2.0 g of PVP K30 in 10 g of absolute ethanol to prepare solution B, and quickly pour solution A into the container containing solution B under the condition that the ultrasonic power density is 0.6 W / cm2, and continue ultrasonic treatment for 30 minutes to obtain an alcohol-based nano silver antibacterial liquid with a nano silver mass concentration of 4.62%.

[0056] Step S2, preparation of hydrophobic liquid. Add 100 g of isopropanol to the container placed in a constant temperature water bath, control the temperature of the constant temperature water bath at 35°C, turn on the stirrer, and sequentially and slowly add 8 g of low-viscosity hydroxyl silicone oil, 1.2 g of 107 glue, and 6 g of hydrogen-containing silicone oil, and continuously stir for 40 minutes to obtain a transparent and colorless solution. Then add 2.0 g of concentrated sulfuric acid and continue stirring and reacting for 60 minutes. Finally, add 0.8 g of hexamethyldisiloxane and stir for 20 minutes to obtain the hydrophobic liquid. The viscosity of the low-viscosity hydroxyl silicone oil is 300 CS, and the hydroxyl content is 9 wt%, and the viscosity of the hydrogen-containing silicone oil is 120 CS, and the hydrogen content is 1.6 wt%.

[0057] Step S3: Preparation of nano silver antibacterial hydrophobic liquid. Add 1.0 g of the high-concentration nano silver antibacterial liquid prepared in Step S1 to 100 g of the hydrophobic liquid prepared in Step S2, stir for 30 minutes to mix evenly, and obtain an antibacterial hydrophobic liquid with a nano silver mass concentration of 457 PPM.

[0058] The laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in Example 1 is as Figure 1 shown. As Figure 1 shown, the D50 size of the nano silver particles prepared in Example 1 is only 5.055 nm, and the size distribution is narrow. From Figure 2 the transmission electron microscope photos, it can be seen that the nano silver particles prepared in Example 1 are spherical, with a small particle size, uniform shape, and good dispersion.

[0059] Figure 3 and Figure 4 are the antibacterial property test of the nano silver antibacterial hydrophobic liquid prepared in Example 1 against Escherichia coli. Compared with the blank control sample, the diameter of the inhibition zone of the nano silver antibacterial hydrophobic liquid can reach up to 27 mm at most, and the antibacterial rate against Escherichia coli is greater than 99.99%, showing excellent antibacterial properties.

[0060] The schematic diagram of the usage method process of the nano silver antibacterial hydrophobic liquid of the present invention is as Figure 5 shown as follows:

[0061] Step S11: Clean the glass surface with clean water and anhydrous ethanol successively to remove surface contaminants and oil stains, etc. After standing until the anhydrous ethanol volatilizes, obtain a clean glass surface.

[0062] Step S12: Drop the nano silver antibacterial hydrophobic liquid prepared by the present invention on the glass surface, and use a dust-free cloth to evenly spin-coat the nano silver antibacterial hydrophobic liquid on the glass surface.

[0063] Step S13: Stand for a period of time until the anhydrous alcohol solvent volatilizes, and then obtain a glass surface with both antibacterial and hydrophobic functions. Optionally, repeat Step S2 several times to obtain a glass surface with better antibacterial and hydrophobic functions.

[0064] Figure 6 are the comparison photos of the hydrophobic angles of the glass before and after coating the antibacterial hydrophobic liquid prepared in Example 1. It can be seen that for the glass spin-coated with the antibacterial hydrophobic liquid prepared in Example 1, the hydrophobic angle increases from 49.085° before coating to 106.103°, showing good hydrophobic and anti-fouling functions.

[0065] In summary, through the integration of antibacterial and hydrophobic dual functions, low-cost production, coating process, and multi-scenario adaptability, the technology of the present invention solves the problems of the limitations of single antibacterial or hydrophobic performance of existing glass and the high cost of overall doping, achieving a breakthrough in the integration of "antibacterial-hydrophobic", and providing a simple and convenient antibacterial and hydrophobic dual-function transformation solution for the existing glass in the fields of electronics, medical, industrial, consumer, construction, automotive, etc.

[0066] Example 2

[0067] Step S1: Preparation of high-concentration alcohol-based nano-silver antibacterial solution. Dissolve 2 g of silver nitrate in a mixed solution of 6 g of absolute ethanol and 6 g of ethylene glycol to prepare solution A, and dissolve 1.6 g of PVP K17 in 8 g of absolute ethanol to prepare solution B. Under the condition of an ultrasonic power density of 0.3 W / cm2, quickly pour solution A into the container containing solution B, and continue ultrasonic treatment for 20 minutes to obtain an alcohol-based nano-silver antibacterial solution with a nano-silver mass concentration of 5.38%.

[0068] Step S2: Preparation of hydrophobic solution. Add 40 g of ethanol and 60 g of isopropanol to the container placed in a constant temperature water bath respectively, control the temperature of the constant temperature water bath at 25 °C, turn on the stirrer, and sequentially and slowly add 4 g of low-viscosity hydroxy silicone oil, 0.5 g of 108 glue, and 2 g of hydrogen-containing silicone oil, and continuously stir for 20 minutes to obtain a transparent and colorless solution. Then add 1.0 g of concentrated sulfuric acid and continue stirring and reacting for 40 minutes. Finally, add 0.1 g of octamethylcyclotetrasiloxane and stir for 10 minutes to obtain a hydrophobic solution. The viscosity of the low-viscosity hydroxy silicone oil is 150 CS, and the hydroxyl content is 8 wt%; the viscosity of the hydrogen-containing silicone oil is 50 CS, and the hydrogen content is 1.2 wt%.

[0069] Step S3: Preparation of nano-silver antibacterial and hydrophobic solution. Add 0.3 g of the high-concentration nano-silver antibacterial solution prepared in step S1 to 100 g of the hydrophobic solution prepared in step S2, and stir for 20 minutes to mix evenly to obtain an antibacterial and hydrophobic solution with a nano-silver mass concentration of 160 PPM.

[0070] The laser particle size diagram of the high-concentration alcohol-based nano-silver antibacterial solution prepared in this example is as Figure 7 shown. It can be seen that the particle size of the nanoparticles prepared in this example is 14.54 nm, and the size distribution is narrow. Spray the prepared hydrophobic antibacterial solution on the cleaned glass plate, and then conduct the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 8 shown. The measured hydrophobic angle is 105.633°. Carry out the antibacterial test of the nano-silver antibacterial and hydrophobic solution of this example against Escherichia coli, and the antibacterial rate against Escherichia coli is greater than 99.1%.

[0071] Example 3

[0072] Step S1, preparation of high-concentration alcohol-based nano-silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 10 g of absolute ethanol and 10 g of ethylene glycol to prepare solution A. Dissolve 3.0 g of PVP K30 in 20 g of absolute ethanol to prepare solution B. Under the condition of an ultrasonic power density of 1.0 W / cm2, quickly pour solution A into the container containing solution B, and continue ultrasonic treatment for 80 minutes to obtain an alcohol-based nano-silver antibacterial liquid with a nano-silver mass concentration of 2.82%.

[0073] Step S2, preparation of hydrophobic liquid. Add 40 g of propylene glycol and 80 g of isopropyl alcohol to the container placed in a constant temperature water bath respectively. Control the temperature of the constant temperature water bath at 40 °C, turn on the stirrer, and sequentially and slowly add 6 g of low-viscosity hydroxy silicone oil, 1.0 g of polyvinyl formal, and 4 g of hydrogen-containing silicone oil, and continuously stir for 50 minutes to obtain a transparent and colorless solution. Then add 1.2 g of concentrated sulfuric acid and continue stirring and reacting for 120 minutes. Finally, add 0.3 g of hexamethylcyclotrisiloxane and stir for 40 minutes to prepare the hydrophobic liquid. The viscosity of the low-viscosity hydroxy silicone oil is 500 CS, and the hydroxy content is 10 wt%. The viscosity of the hydrogen-containing silicone oil is 80 CS, and the hydrogen content is 2.0 wt%.

[0074] Step S3, preparation of nano-silver antibacterial hydrophobic liquid. Add 1.5 g of the high-concentration nano-silver antibacterial liquid prepared in Step S1 to 100 g of the hydrophobic liquid prepared in Step S2, and stir for 50 minutes to mix evenly to obtain an antibacterial hydrophobic liquid with a nano-silver mass concentration of 416 PPM.

[0075] The laser particle size diagram of the high-concentration alcohol-based nano-silver antibacterial liquid prepared in this example is as Figure 9 shown. It can be seen that the particle size of the nano-particles prepared in this example is 5.208 nm, and the size distribution is narrow. Spray the prepared hydrophobic antibacterial liquid on the cleaned glass plate, and then conduct the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 10 shown. The measured hydrophobic angle is 103.840°. Conduct an antibacterial test on Escherichia coli with the nano-silver antibacterial hydrophobic liquid of this example, and the antibacterial rate against Escherichia coli is greater than 99.99%.

[0076] Example 4

[0077] Step S1, preparation of high-concentration alcohol-based nano-silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 8 g of absolute ethanol and 10 g of ethylene glycol to prepare solution A. Dissolve 1.2 g of PVP K60 in 12 g of absolute ethanol to prepare solution B. Under the condition of an ultrasonic power density of 0.5 W / cm2, quickly pour solution A into the container containing solution B, and continue ultrasonic treatment for 50 minutes to obtain an alcohol-based nano-silver antibacterial liquid with a nano-silver mass concentration of 3.83%.

[0078] Step S2, preparation of hydrophobic liquid. Add 95 g of ethanol and 5 g of ethylene glycol into a container placed in a constant temperature water bath respectively. Control the temperature of the constant temperature water bath at 30 °C. Turn on the stirrer and sequentially and slowly add 10 g of low-viscosity hydroxy silicone oil, 2.0 g of polyvinyl butyral, and 8 g of hydrogen-containing silicone oil. Continuously stir for 80 minutes to obtain a transparent and colorless solution. Then add 4.0 g of concentrated sulfuric acid and continue stirring and reacting for 90 minutes. Finally, add 1.0 g of hexamethyldisiloxane and stir for 40 minutes to prepare the hydrophobic liquid. The viscosity of the low-viscosity hydroxy silicone oil is 800 CS, and the hydroxy content is 8 wt%. The viscosity of the hydrogen-containing silicone oil is 20 CS, and the hydrogen content is 1.0 wt%.

[0079] Step S3, preparation of nano-silver antibacterial hydrophobic liquid. Add 0.8 g of the high-concentration nano-silver antibacterial liquid prepared in Step S1 into 100 g of the hydrophobic liquid prepared in Step S2, and stir for 40 minutes to mix evenly to obtain an antibacterial hydrophobic liquid with a nano-silver mass concentration of 304 PPM.

[0080] The laser particle size diagram of the high-concentration alcohol-based nano-silver antibacterial liquid prepared in this example is as Figure 11 shown. It can be seen that the particle size of the nano-particles prepared in this example is 13.07 nm, and the size distribution is narrow. Spray the prepared hydrophobic antibacterial liquid on the cleaned glass plate, and then conduct the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 12 shown. The measured hydrophobic angle is 105.331°. Conduct an antibacterial property test on the nano-silver antibacterial hydrophobic liquid of this example against Escherichia coli, and the antibacterial rate against Escherichia coli is greater than 99.9%.

[0081] Example 5

[0082] Step S1, preparation of high-concentration alcohol-based nano-silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 10 g of absolute ethanol and 8 g of ethylene glycol to prepare solution A, and dissolve 2.4 g of PVP K90 in 18 g of absolute ethanol to prepare solution B. Under the condition of an ultrasonic power density of 0.8 W / cm 2 Quickly pour solution A into a container containing solution B, and continue ultrasonic treatment for 60 minutes to obtain an alcohol-based nano-silver antibacterial liquid with a nano-silver mass concentration of 3.14%.

[0083] Step S2, preparation of hydrophobic liquid. Add 5 g of glycerol and 95 g of isopropanol into a container placed in a constant temperature water bath respectively. Control the temperature of the constant temperature water bath at 50 °C, turn on the stirrer, and sequentially and slowly add 7 g of low-viscosity hydroxy silicone oil, 1.8 g of 107 rubber, and 5 g of hydrogen-containing silicone oil, and continuously stir for 50 minutes to obtain a transparent and colorless solution. Then add 2.5 g of concentrated sulfuric acid and continue to stir and react for 110 minutes. Finally, add 0.7 g of polydimethylsiloxane and stir for 30 minutes to prepare the hydrophobic liquid. The viscosity of the low-viscosity hydroxy silicone oil is 600 CS, and the hydroxy content is 8.5 wt%. The viscosity of the hydrogen-containing silicone oil is 30 CS, and the hydrogen content is 1.5 wt%.

[0084] Step S3, preparation of nano-silver antibacterial hydrophobic liquid. Add 1.0 g of the high-concentration nano-silver antibacterial liquid prepared in Step S1 into 100 g of the hydrophobic liquid prepared in Step S2, and stir for 20 minutes to mix evenly to prepare an antibacterial hydrophobic liquid with a nano-silver mass concentration of 310 PPM.

[0085] The laser particle size diagram of the high-concentration alcohol-based nano-silver antibacterial liquid prepared in this example is as Figure 13 shown. It can be seen that the particle size of the nanoparticles prepared in this example is 5.652 nm, and the size distribution is narrow. Spray the prepared hydrophobic antibacterial liquid on the cleaned glass plate, and then conduct the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 14 shown. The measured hydrophobic angle is 105.988°. Conduct an antibacterial test on Escherichia coli with the nano-silver antibacterial hydrophobic liquid of this example, and the bacteriostatic rate against Escherichia coli is greater than 99.9%.

[0086] Example 6

[0087] Step S1, preparation of high-concentration alcohol-based nano-silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 10 g of absolute ethanol and 8 g of ethylene glycol to prepare solution A, dissolve 2.2 g of PVP K17 in 10 g of absolute ethanol to prepare solution B. Under the condition of an ultrasonic power density of 0.7 W / cm2, quickly pour solution A into a container containing solution B, and continue ultrasonic treatment for 40 minutes to prepare an alcohol-based nano-silver antibacterial liquid with a nano-silver mass concentration of 3.93%.

[0088] Step S2, Preparation of hydrophobic liquid. Add 15 g of butanol and 85 g of isopropanol into a container placed in a constant temperature water bath respectively. Control the temperature of the constant temperature water bath at 40 °C, turn on the stirrer, and sequentially and slowly add 9 g of low-viscosity hydroxyl silicone oil, 0.8 g of 107 glue, and 6.5 g of hydrogen-containing silicone oil. Continuously stir for 60 minutes to obtain a transparent and colorless solution. Then add 3.0 g of concentrated sulfuric acid and continue stirring and reacting for 100 minutes. Finally, add 0.9 g of hexamethyldisiloxane and stir for 40 minutes to prepare the hydrophobic liquid. The viscosity of the low-viscosity hydroxyl silicone oil is 300 CS, and the hydroxyl content is 9 wt%. The viscosity of the hydrogen-containing silicone oil is 30 CS, and the hydrogen content is 1.5 wt%.

[0089] Step S3, Preparation of nano silver antibacterial hydrophobic liquid. Add 1.2 g of the high-concentration nano silver antibacterial liquid prepared in Step S1 into 100 g of the hydrophobic liquid prepared in Step S2, and stir for 20 minutes to mix evenly to obtain an antibacterial hydrophobic liquid with a nano silver mass concentration of 466 PPM.

[0090] The laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in this example is as Figure 15 shown. It can be seen that the particle size of the nanoparticles prepared in this example is 8.759 nm, and the size distribution is narrow. Spray the prepared hydrophobic antibacterial liquid on the cleaned glass plate, and then conduct the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 16 shown. The measured hydrophobic angle is 105.142°. Conduct an antibacterial property test on Escherichia coli with the nano silver antibacterial hydrophobic liquid of this example, and the antibacterial rate against Escherichia coli is greater than 99.99%.

[0091] Comparative Example 1

[0092] A nano silver antibacterial hydrophobic liquid, and its preparation method includes the following steps:

[0093] Step S1, Preparation of high-concentration alcohol-based nano silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 6 g of absolute ethanol and 4 g of ethylene glycol to prepare solution A, and dissolve 0.9 g of PVP K30 in 8 g of absolute ethanol to prepare solution B. Under the condition of an ultrasonic power density of 0.2 W / cm 2 Pour solution A quickly into the container containing solution B, and continue ultrasonic treatment for 40 minutes to prepare an alcohol-based nano silver antibacterial liquid with a nano silver mass concentration of 6.08%.

[0094] Step S2, preparation of hydrophobic liquid. Add 15 g of butanol and 85 g of isopropanol into a container placed in a constant temperature water bath respectively. Control the temperature of the constant temperature water bath at 60 °C, turn on the stirrer, and sequentially and slowly add 3 g of low-viscosity hydroxy silicone oil, 1.8 g of 107 glue, and 1.5 g of hydrogen-containing silicone oil. Continuously stir for 60 minutes to obtain a transparent and colorless solution. Then add 5.0 g of concentrated sulfuric acid and continue to stir and react for 100 minutes. Finally, add 0.1 g of hexamethyldisiloxane and stir for 40 minutes to prepare the hydrophobic liquid. The viscosity of the low-viscosity hydroxy silicone oil is 80 CS, and the hydroxy content is 5 wt%. The viscosity of the hydrogen-containing silicone oil is 50 CS, and the hydrogen content is 0.6 wt%.

[0095] Step S3, preparation of nano silver antibacterial hydrophobic liquid. Add 1.0 g of the high-concentration nano silver antibacterial liquid prepared in Step S1 into 100 g of the hydrophobic liquid prepared in Step S2, and stir for 20 minutes to mix evenly to obtain an antibacterial hydrophobic liquid with a nano silver mass concentration of 602 PPM.

[0096] The laser particle size diagram of the high-concentration alcohol-based nano silver antibacterial liquid prepared in this comparative example is as Figure 17 shown. It can be seen that the particle size distribution of the nanoparticles prepared in this comparative example shows a bimodal peak, the distribution is relatively wide, and the proportion of large particles is relatively large. Spray the prepared hydrophobic antibacterial liquid on the cleaned glass plate, and then perform the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 18 shown. The measured hydrophobic angle is 55.308°. Conduct an antibacterial test on Escherichia coli with the nano silver antibacterial hydrophobic liquid of this comparative example, and the antibacterial rate against Escherichia coli is greater than 89.6%.

[0097] Comparative Example 2

[0098] A nano silver antibacterial hydrophobic liquid, and its preparation method includes the following steps:

[0099] Step S1, preparation of high-concentration alcohol-based nano silver antibacterial liquid. Dissolve 2 g of silver nitrate in a mixed solution of 20 g of absolute ethanol and 6 g of ethylene glycol to prepare solution A, dissolve 0.6 g of PVP K90 in 30 g of absolute ethanol to prepare solution B. Under the condition that the ultrasonic power density is 0.2 W / cm 2 Quickly pour solution A into the container containing solution B, and continue ultrasonic treatment for 40 minutes to obtain an alcohol-based nano silver antibacterial liquid with a nano silver mass concentration of 2.17%.

[0100] Step S2, preparation of hydrophobic liquid. Add 100 g of isopropanol into a container placed in a constant temperature water bath. Control the temperature of the constant temperature water bath at 35°C. Turn on the stirrer and sequentially and slowly add 12 g of low-viscosity hydroxy silicone oil, 2.6 g of 107 glue, and 3.5 g of hydrogen-containing silicone oil. Continuously stir for 70 minutes to obtain a transparent and colorless solution. Then add 5.0 g of concentrated sulfuric acid and continue stirring and reacting for 90 minutes. Finally, add 0.4 g of hexamethylcyclotrisiloxane and stir for 35 minutes to prepare the hydrophobic liquid. The viscosity of the low-viscosity hydroxy silicone oil is 150 CS, and the hydroxy content is 8 wt%. The viscosity of the hydrogen-containing silicone oil is 120 CS, and the hydrogen content is 1.6 wt%.

[0101] Step S3, preparation of nano-silver antibacterial hydrophobic liquid. Add 1.0 g of the high-concentration nano-silver antibacterial liquid prepared in Step S1 into 100 g of the hydrophobic liquid prepared in Step S2, and stir for 20 minutes to mix evenly to obtain an antibacterial hydrophobic liquid with a nano-silver mass concentration of 215 PPM.

[0102] The laser particle size diagram of the high-concentration alcohol-based nano-silver antibacterial liquid prepared in this comparative example is as Figure 19 shown. It can be seen that the particle size of the nano-particles prepared in this comparative example shows a bimodal peak, with a relatively wide distribution and a relatively large proportion of large particles. Spray the prepared hydrophobic antibacterial liquid on the cleaned glass plate, and then conduct the detection of the hydrophobic angle. The steps are the same as those in Example 1, and the results are as Figure 20 shown. The measured hydrophobic angle is 88.660°. Conduct an antibacterial property test on the nano-silver antibacterial hydrophobic liquid of this comparative example against Escherichia coli, and the antibacterial rate against Escherichia coli is greater than 73.6%.

[0103] It can be seen from the comparison of the above examples and comparative examples that the examples adopting the technical solution of the present invention have better antibacterial and hydrophobic dual functions, with excellent long-term antibacterial and hydrophobic properties.

[0104] The above content is a further detailed description of the present invention in combination with specific preferred embodiments. It cannot be determined that the specific implementation of the present invention is only limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or substitutions can be made, which should all be regarded as belonging to the protection scope of the present invention.

Claims

1. A preparation method of a nano-silver antibacterial hydrophobic liquid, characterized in that: It includes the following steps: Step S1: Dissolve silver nitrate in the first anhydrous alcohol solvent to prepare solution A, and dissolve polyvinylpyrrolidone in the second anhydrous alcohol solvent to prepare solution B; mix solution A and solution B, and perform ultrasonic treatment for 20 - 80 minutes to obtain a high-concentration alcohol-based nano-silver antibacterial liquid, where the concentration of silver in the high-concentration alcohol-based nano-silver antibacterial liquid is 2.8 - 5.5 wt.%. Step S2: Add low-viscosity hydroxy silicone oil, polyvinyl acetal, and hydrogen-containing silicone oil to the third anhydrous alcohol solvent and stir to form a transparent and colorless solution; then add concentrated sulfuric acid, continue to stir and react for 40 - 120 minutes, and finally add siloxane and stir for 10 - 40 minutes to obtain a hydrophobic liquid; among them, the hydroxy content of the low-viscosity hydroxy silicone oil is 8 - 10 wt%, and the viscosity is 100 - 800 CS; the hydrogen content of the hydrogen-containing silicone oil is 1 - 2 wt%, and the viscosity is less than 200 CS. Step S3: Add the high-concentration alcohol-based nano-silver antibacterial liquid prepared in Step S1 to the hydrophobic liquid prepared in Step S2, stir and mix evenly to obtain a nano-silver antibacterial hydrophobic liquid; in the nano-silver antibacterial hydrophobic liquid, the mass concentration of nano-silver particles is 150 - 500 PPM.

2. The preparation method of the nano silver antibacterial hydrophobic liquid according to claim 1, characterized in that: In Step S1, the first anhydrous alcohol solvent and the second anhydrous alcohol solvent are one or more mixtures of ethanol, ethylene glycol, isopropanol, propylene glycol, glycerol, and butanol, and the polyvinylpyrrolidone is one or more mixtures of those with polymerization degrees of K17, K30, K60, and K90.

3. The preparation method of the nano-silver antibacterial hydrophobic liquid according to claim 2, characterized in that: In Step S1, the mass ratio of silver nitrate, PVP, the sum of the first anhydrous alcohol solvent and the second anhydrous alcohol solvent is 1:0.6 - 1.5:10 - 20.

4. The preparation method of the nano-silver antibacterial hydrophobic liquid according to claim 3, characterized in that: In step S1, the frequency of the ultrasonic wave is 40KHz, and the power density is 0.3 - 1.0W / cm 2 .

5. The preparation method of the nano-silver antibacterial hydrophobic liquid according to claim 1, characterized in that: In Step S2, the mass ratio of the second anhydrous alcohol solvent, low-viscosity hydroxy silicone oil, polyvinyl acetal, hydrogen-containing silicone oil, concentrated sulfuric acid, and siloxane is 100:4 - 10:0.5 - 2.0:2 - 8:1 - 4:0.1 - 1.

0.

6. The preparation method of the nano silver antibacterial hydrophobic liquid according to claim 5, wherein: In Step S2, the third anhydrous alcohol solvent is one or more mixtures of ethanol, ethylene glycol, isopropanol, propylene glycol, glycerol, and butanol; the polyvinyl acetal is one of 107 glue, 108 glue, polyvinyl acetal methyl ethyl aldehyde, and polyvinyl butyral; the siloxane is at least one of polydimethylsiloxane, hexamethyldisiloxane, octamethylcyclotetrasiloxane, and hexamethylcyclotrisiloxane.

7. The preparation method of the nano-silver antibacterial hydrophobic liquid according to claim 6, characterized in that: In Step S2, add low-viscosity hydroxy silicone oil, polyvinyl acetal, and hydrogen-containing silicone oil to the third anhydrous alcohol solvent and stir in a constant temperature water bath, and the temperature of the water bath is 25 - 50 °C.

8. A nano-silver antibacterial hydrophobic liquid, characterized in that: It is prepared by using the preparation method of the nano-silver antibacterial hydrophobic liquid described in any one of claims 1 - 7.

9. The application of the nano-silver antibacterial hydrophobic liquid according to claim 8, characterized in that: It is used for coating on the glass surface to make the glass surface have antibacterial and hydrophobic functions.

10. Use of the nano-silver antibacterial hydrophobic liquid according to claim 9, characterized in that: It includes the following steps: Step S11: Clean the glass surface to obtain a clean glass surface. Step S12: Spray or drop the nano-silver antibacterial hydrophobic liquid on the glass surface, and evenly spin-coat the nano-silver antibacterial hydrophobic liquid on the glass surface with a dust-free cloth or a cleaning sponge. Step S13: Let it stand until the anhydrous alcohol solvent volatilizes to obtain a glass surface with both antibacterial and hydrophobic functions.

Citation Information

Cited By

  • Antibacterial type anti-fingerprint agent additive, preparation method and application thereof

    CN122772012A